The Relationship between Exclusive Breastfeeding and Tonsillitis in Children aged 0-7 Years - Wardhani, Hanni; Rachmasari, Melati Citra; Puryani, Agustina (Journal of Maternal and Child Health, 2020)
Background: Tonsillitis is a type of acute res